2018
DOI: 10.1088/1361-6544/aa999f
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative recurrence for free semigroup actions

Abstract: We consider finitely generated free semigroup actions on a compact metric space and obtain quantitative information on Poincaré recurrence, average first return time and hitting frequency for the random orbits induced by the semigroup action. Besides, we relate the recurrence to balls with the rates of expansion of the semigroup's generators and the topological entropy of the semigroup action. Finally, we establish a partial variational principle and prove an ergodic optimization for this kind of dynamical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Relative metric entropy of a semigroup action. In this section we will recall the notion of relative metric entropy proposed by Abramov and Rokhlin in [1], which was later adopted in [18] and [17] and whose connection with the topological entropy of the semigroup action was explored in [10].…”
Section: Measure Theoretical Entropy Of a Semigroup Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Relative metric entropy of a semigroup action. In this section we will recall the notion of relative metric entropy proposed by Abramov and Rokhlin in [1], which was later adopted in [18] and [17] and whose connection with the topological entropy of the semigroup action was explored in [10].…”
Section: Measure Theoretical Entropy Of a Semigroup Actionmentioning
confidence: 99%
“…Denote by M G the set of Borel probability measures on X invariant by g i , for all i ∈ {1, • • • , p}. In [10], it was shown that sup ν ∈ M G h (1) ν (S, P) ≤ h top (S) + (log p − h P (σ)) .…”
Section: Measure Theoretical Entropy Of a Semigroup Actionmentioning
confidence: 99%
See 3 more Smart Citations